Influence of post-exercise hot-water therapy on adaptations to training over 4 weeks in elite short-track speed skaters - Thibaut, M.; Solsona, R.; Antonietti, J.-P.; Borrani, F.; Candau, R.; Sanchez, A. M. J. (Journal of Exercise Science & Fitness, 2021)
Background/Objective: This study aimed to investigate the effects of regular hot water bathing (HWB), undertaken 10 min after the last training session of the day, on chronic adaptations to training in elite athletes. Methods: Six short-track (ST) speed skaters completed four weeks of post-training HWB and four weeks of post-training passive recovery (PR) according to a randomized cross-over study. During HWB, participants sat in a jacuzzi (40 °C; 20 min). Results: According to linear mixed models, maximal isometric strength of knee extensor muscles was significantly increased for training with HWB (p < 0.0001; d = 0.41) and a tendency (p = 0.0529) was observed concerning VO2max no significant effect of training with PR or HWB was observed for several variables (p > 0.05), including aerobic peak power output, the decline rate of jump height during 1 min-continuous maximal countermovement jumps (i.e. anaerobic capacity index), and the force-velocity relationship. Regarding specific tasks on ice, a small effect of training was found on both half-lap time and total time during a 1.5-lap all-out exercise (p = 0.0487; d = 0.23 and p = 0.0332; d = 0.21, respectively) but no additional effect of HWB was observed. Conclusion: In summary, the regular HWB protocol used in this study can induce additional effects on maximal isometric strength without compromising aerobic and anaerobic adaptations or field performance in these athletes.